2012
DOI: 10.1155/2012/581531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Minimental State Examination Scale and the International HIV Dementia Scale in Assessing Cognitive Function in Nigerian HIV Patients on Antiretroviral Therapy

Abstract: Introduction. HIV-associated neurocognitive disorder (HAND) remains common despite the availability of antiretroviral therapy. Routine screening will improve early detections. Objective. To compare the performance of the minimental state examination (MMSE) and international HIV dementia scale (IHDS) in assessing neurocognitive function in HIV/AIDS patients on antiretroviral therapy. Methods. A case-control study of 208 HIV-positive and 121 HIV-negative individuals. Baseline demographic data were documented and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
3
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
9
25
3
6
Order By: Relevance
“…Yet, it is important to note that the high prevalence of neurocognitive deficit in this study may reflect the need for further refinement of the tool, IHDS, at national level. As compared to prior studies, the current finding is similar with the result of a study conducted in India (32.5%) (18), a study done in Nigeria (34.4%) [28] and an earlier Metaanalysis (systemic review) in Sub-Saharan area (30.9%) (2). However, it is less than the findings of previous studies undertaken in Botswana (38%) (21), a study in the international community (37%) (15), a study done in Cameroon (85%) [29], a study conducted in Asia (90%) (19) and a Ugandan study (46.49%) (30,31,32).…”
Section: Discussionsupporting
confidence: 90%
“…Yet, it is important to note that the high prevalence of neurocognitive deficit in this study may reflect the need for further refinement of the tool, IHDS, at national level. As compared to prior studies, the current finding is similar with the result of a study conducted in India (32.5%) (18), a study done in Nigeria (34.4%) [28] and an earlier Metaanalysis (systemic review) in Sub-Saharan area (30.9%) (2). However, it is less than the findings of previous studies undertaken in Botswana (38%) (21), a study in the international community (37%) (15), a study done in Cameroon (85%) [29], a study conducted in Asia (90%) (19) and a Ugandan study (46.49%) (30,31,32).…”
Section: Discussionsupporting
confidence: 90%
“…We have demonstrated that both the IHDS and CAT-rapid are useful in screening for HIV-D. We confirm, as others have, that the MMSE has relatively poor sensitivity [20, 30]. No single tool proved to be ideal in screening for symptomatic HAND, although the CAT-rapid displayed fair sensitivity (78 %) with only weak specificity (54 %), while the IHDS showed weak sensitivity (52 %) and good specificity (86 %).…”
Section: Discussionsupporting
confidence: 84%
“…Among PLHIV with NCD, the average score was 9 and in the US cohort (9.3) as well as in the Ugandan cohort when it was 9.9 [11]. Our finding is similar to that reported in Nigeria (8.36) by Oshinaike Olajumoke et al [31], in Cameroon (9.4) by Njamnshi et al [27]. This argues for the universality of the use of IHDS.…”
Section: The Performance Of Patients To Different Testssupporting
confidence: 88%
“…But it is the IHDS is advised. Furthermore IHDS compared the MMSE (Mini Mental State Examination) detect much on the NCD HIV field [31]. Note that HIV-related dementia has an annual incidence of 7% after development of AIDS and ultimately affects 20% of people infected with HIV.…”
Section: Prevalencementioning
confidence: 99%